O estudo de simetrias com frisos e questões da OBMEP - Nardelli, Renan Eduardo (2015)
This work handles topics involving geometric transformations and friezes for the study of symmetry. It aimed to present students from the Ninth Grade of a public school in São Paulo State activities, in order to enrich them scientifically, culturally; sharpening their curiosity and critical reasoning. For this, a series of activities related to the theme symmetry was developed: first of all, students solved questions on a diagnosing sheet of paper about translation, reflection and rotation movements on the plan, followed by a slide presentation of these same topics. Then, they watched a video about Alhambra Palace in Spain to motivate them to study the symmetries in decorative friezes. Students solved various problems of OBMEP involving symmetrical situations and they ended up the work building seven patterns of friezes. The analysis of these solutions is presented in order to verify whether there was a contribution to the learning of geometric transformations related to symmetries. Such analysis is based on the researcher’s experience and also on testimonials from the participants.